Enhanced bacteriostatic effects of phage vB_C4 and cell wall-targeting antibiotic combinations against drug-resistant Aeromonas veronii - Xin Cao; Yanqiong Tang; ZhenZhang Lu; Xiang Ma; Hong Li; Xue Chi; Juanjuan Li; Zhu Liu (Microbiology Spectrum)
ABSTRACT Aeromonas veronii is a vital zoonotic pathogen known for its extensive drug resistance and ability to form biofilms, which contribute to its antibiotic resistance. In this study, the phage vB_C4, specifically targeting A. veronii, was isolated and subjected to bioinformatic analysis and bacteriostatic activity assays. The combination of phage vB_C4 with antibiotics such as cephalothin and cefoxitin, which target the bacterial cell wall, resulted in a significantly enhanced bacteriostatic effect compared to either the phage or antibiotics alone. Furthermore, the phage dosage was critical in optimizing the antimicrobial effect when used in conjunction with antibiotics. This combined treatment exhibited a more distinct effect in removing mature biofilms and inhibiting biofilm formation, leading to a considerable decrease in bacterial density within the biofilm. Overall, the synergistic use of phage and antibiotics offers a novel attitude for treating pathogenic bacteria and holds significant potential in preventing the emergence of drug-resistant strains.IMPORTANCEThe combined application of phages and antibiotics not only effectively inhibits the emergence of phage-resistant bacteria but also reduces the required effective concentration of antibiotics. Additionally, this combination therapy demonstrates significant therapeutic effects on clinical infections mediated by biofilms. Consequently, this study establishes a basis for evaluating the parameters essential for utilizing phage-antibiotic combination therapy in the treatment of biofilm-associated infections, thereby offering a novel selection for the clinical management of multidrug-resistant bacterial infections.